Over a million students use our free study notes to help them with their homework
We have X2 - 4X = 5, write the expression on the left side as X2 - 2•2X = 5. Then we would need extra term 4 to complete the square, so adding 4 on the both sides gives us, X2Answered by Rabin K. • Maths tutor3109 Views
This is a simple integration, integrating each individual term with respect to x.For the cos(4x), you should use 'integration by substitution' as it is a function of a function.cos(4x) = cos(u) and u = 4x...
When doing double integration with two arbitrary variables, for example 'x' and 'y' look at the Integration on the inside and integrate the function between the given range. For example if the integrand i...
You might be tempted to start by expanding the brackets, but in this case it's much easier to use the chain rule. This is the rule that, to differentiate f(g(x)), we find f'(g(x))*g'(x). In other words, t...
x2 = 4(x-3)2x2 = 4(x-3)(x-3) - showing that these are double bracketsx2 = 4(x2 - 6x + 9) - expanding the double bracketsx2 = 4x2Answered by Emily L. • Maths tutor3130 Views
←
538
539
540
541
542
→
Internet Safety
Payment Security
Cyber
Essentials